Integrating and Querying OpenStreetMap and Linked Geo Open Data. (23rd September 2017) - Almendros-Jiménez, Jesús M; Becerra-Terón, Antonio; Torres, Manuel
Abstract: In recent years, Open Street Map (OSM) has evolved into a highly popular geospatial system. The key of success of OSM is that OSM is open to absolutely everyone. OSM is not dependent on any one government, company, university or international organization. OSM is based on crowdsourcing, in which users collaborate to collect spatial data of urban and rural areas on the earth. With the arising of Linked Open Data (LOD) initiative, and more concretely with Linked Geo Open Data (LGOD), many Web resources have been made available to everyone, providing geo-located datasets. In this paper, a framework, called XOSM ( XQuery for OpenStreetMap ), for integrating and querying OSM and LGOD resources, is presented. The framework is equipped with a Web tool and a rich XQuery-based library, enabling the definition of queries combining OSM layers and layers created from LGOD resources (KML, GeoJSON, CSV and RDF (and also XML)). The framework also provides an API to execute XQuery queries using the library.